Panchagavya and Andrographis paniculata as Alternatives to Antibiotic Growth Promoter on Broiler Production and Carcass Characteristics - Mathivanan, R.; Edwin, S.C.; Amutha, R.; Viswanathan, K. (International Journal of Poultry Science, 2006)
A biological experiment was conducted to study the effect of panchagavya and Andrographis paniculata as alternatives to antibiotic growth promoter on broiler production and carcass characteristics with one hundred and eighty commercial, straight run day-old broiler chicks. The chicks were fed basal diet (T1), basal diet with virginiamycin -20 mg/kg (T2), basal diet with panchagavya -7.5 g/kg (T3), basal diet with A. paniculata -2.0 g/kg (T4), basal diet with probiotics -0.5 g/kg (T5) and basal diet with mannanoligosaccharide (MOS) - 2.0 g/kg from 1 to 28 days and 0.5 g/kg from 29 to 42 days growing period (T6) for 6 weeks period. The result revealed that the mean body weight and weight gain of T6, T5 and T3 groups were significantly (P